THE PRELIMINARY IDENTIFICATION CHARACTERS OF SOME COLLEMBOLA FROM VARANASI REGION OF UTTAR PRADESH, INDIA - SANTESHWARI; M. RAGHURAMAN; J. SINGH (The Bioscan, 2013)
The Collembolans are major part of soil biota. Their collection and identification require expertise hands to know the status of soil biota. Therefore, in present study Collembola fauna of different vegetation in Varanasi district of Uttar Pradesh region was studied from March, 2010 to March, 2012. Collembola specimens belonging to 13 genera under 8 families were collected. The predominant families were Hypogastruridae, Isotomidae, Entomobryidae, Paronellidae, Cyphoderidae, Neelidae, Sminthurididae and Katiannidae. The common identified genera are Hypogastrura, Folsomia, Folsomides, Isotomurus, Isotoma, Entomobrya, Seira, Salina, Lepidocyrtus, Cyphoderus, Neelus, Sminthurides and Sminthurinus. The preliminary identification characters of these genera are discussed in the paper.